Enhancing Farm Household Income Through Efficient Arabica Coffee Cultivation in Simalungun, North Sumatera - Martial, Tri; Harmain, Ummu; Harahap, Ahmad Rizki; Musika, Mitra; Tirtana, Mhd Arief (Jurnal AGRISEP, 2024)
North Sumatera is the largest producer of arabica coffee in Indonesia with 29%. However, coffee farmers are always faced with various field problems such as high fertilizer prices, declining production and various traditional cultivation practices that cause low productivity levels. So that in maintaining overall cropping it is necessary to know the efficiency of farm management with efficient coffee management it can increase farmer income, improve the quality of life of farmers, absorb labor, reduce costs and create a sustainable system. The method used in this research is to use the Data Envelopment Analysis (DEA) model to determine the efficient value and the Ordinary Least Squares (OLS) model to determine the efficient influence. The results of this research with the DEA model show that from a total of 133 respondents, the inefficient value is 51%, low efficient 25%, medium efficient 13%, and low efficient 11%. While the OLS model shows that the total cost and total income of farmers can significantly affect the efficiency value, the total production of farmers has no influence on the efficiency value. The research findings imply that improving efficiency requires modernizing technology to overcome traditional management such as the use of superior seeds and fertilizer inputs to increase land production. It also requires the support of relevant policies and institutions that are able to guarantee the availability of production facilities such as superior seeds and fertilizers that are easily available to farmers at affordable prices.